Paper Waste Reduction Efforts Through Digitalization - Iswanto, Rendy (VCD, 2019)
Paper waste reduction efforts through digitalization. Waste is an endless problem to dealt with, through the ages, humankind necessities have escalated, and with the escalation of humankind necessities, the waste produced by humankind has also escalated. The more advanced a civilization, the more waste is produced. Paper waste is one of the wastes. Paper has becoming a basic need for human which is used as a media for communicating and exchanging information. But to produce paper, a large number of trees had to be cut down, alongside of the byproduct waste come out from producing it. Also, the harmful effect of unhappiness of the paper waste which is one of the main causes of the global warming. Therefore, an act of reducing paper waste is needed. Digitalization is one of the options to reduce paper waste. The definition of digitalization is a process to convert printed form, audio form, and video form to digital form. The purpose of digitalization is to aim for efficiency and optimization for storage purpose, security purpose.